The development and use of microsatellite markers for genetic analysis and plant breeding with emphasis on bread wheat - Gupta, P.K.; Varshney, R.K. (Euphytica, 2000)
In recent years, a variety of molecular markers, based on microsatellites or simple sequence repeats (SSRs) have become the markers of choice, thus necessitating their development and use in a variety of plant systems. In this review, the basic principles underlying different hybridization-based (oligonucleotide fingerprinting) and PCR based approaches (STMS, MP-PCR, AMP-PCR/ ISSR/ ASSR, RAMPs/ dRAMPs, SAMPL), making use of microsatellites, have been outlined. Different methods for enrichment of genomic libraries for microsatellites have also been outlined. Relevant literature on the subject, giving a summary of results obtained using each approach, has been reviewed and critically discussed. The review also includes a discussion on literature, which deals with the use of microsatellites in genome mapping, gene tagging, DNA fingerprinting, characterization of germplasm and cytogenetics research. Special emphasis has been laid on the genome of bread wheat, where the work done in the authors' own laboratory has also been briefly reviewed.[PUBLICATION ABSTRACT]